2004
DOI: 10.1088/0967-3334/25/6/014
|View full text |Cite
|
Sign up to set email alerts
|

Image-based carotid flow reconstruction: a comparison between MRI and ultrasound

Abstract: Atherosclerosis is a major cause of morbidity and mortality. Its apparent link with wall shear stress (WSS) has led to considerable interest in the in vivo estimation of WSS. Determining WSS by combining medical images with computational fluid dynamics (CFD) simulations can be performed both with magnetic resonance imaging (MRI) and three-dimensional ultrasound (3DUS). This study compares predicted 3D flow patterns based on black blood MRI and 3DUS. Velocity fields in the carotid arteries of nine subjects have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…1, left) of the left main coronary bifurcation was manufactured post-mortem in the Pathology Department of the Dr. C.J. Finlay Klinik, Havana, Cuba under a defined transmural pressure of 100 mmHg (13,330 Pa) in a specially constructed apparatus using the two-component polymer Technovit 7143 (Heraues Kulzer GmbH, Wehrheim, Germany). The apparatus and the procedure of the vessel casts fabrication were presented elsewhere in detail.…”
Section: Reconstruction and Fabrication Of The Original Phantom Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…1, left) of the left main coronary bifurcation was manufactured post-mortem in the Pathology Department of the Dr. C.J. Finlay Klinik, Havana, Cuba under a defined transmural pressure of 100 mmHg (13,330 Pa) in a specially constructed apparatus using the two-component polymer Technovit 7143 (Heraues Kulzer GmbH, Wehrheim, Germany). The apparatus and the procedure of the vessel casts fabrication were presented elsewhere in detail.…”
Section: Reconstruction and Fabrication Of The Original Phantom Modelmentioning
confidence: 99%
“…Considering regions with the low WSS, we assumed a threshold value of about 0.4-0.5 Pa, which separates the surface area in hemodynamically safe and regions at risk (below threshold value) for atherogenesis 13,14 (see ''Discussion'' section). The analysis shows that 54% of the LCA surface is at risk in the original geometry.…”
Section: Hemodynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This results in gene alterations which in turn causes structural changes of the endothelial cells. A detailed study [37] on flow in carotid arteries has determined some of the important hemodynamic factors (WSS, WSSG) by combining medical images (obtained using magnetic MRI and 3D ultrasound) with CFD simulations. Their results were closely in agreement with those of Malek et al [38], who showed that values of WSS below 0.4 N/m 2 are known to stimulate proatherogenic endothelial phenotype while WSS > 1.5 N/m 2 is found to induce endothelial quiescence.…”
Section: Wss Spatial Wssg and Atherosclerosismentioning
confidence: 99%